The use of acute exercise interventions as game day priming strategies to improve physical performance and athlete readiness in team-sport athletes: A systematic review - Mason, B.; McKune, A.; Pumpa, K.; Ball, N. (Sports Medicine, 2020)
Background: The use of exercise as a priming strategy to enhance sport performance is becoming increasingly popular in professional sports and as an area of research interest. Early research suggests that the acute physiological responses to exercise can positively influence performance for up to 48 h. There is yet to be a comprehensive review of exercise strategies which could be implemented specifically on the day of competition. Objectives: The aim of this systematic review was to provide a synthesis of research investigating acute exercise interventions as game day priming strategies for team-sport athletes to improve physical performance and athlete readiness when implemented in the 1-12 h prior to competition. Methods: A literature search of SPORTDiscus, PubMed and Cochrane Central Register for Controlled Trials was conducted. A total of 6428 studies were retrieved and assessed against the following inclusion criteria: (1) randomised controlled trials and non-randomised comparative studies with reported pre-post intervention outcomes; (2) exercise interventions were applied 1-12 h prior to the assessment of outcome measures. Studies were excluded if they used nutrition, supplementation, pre-heating, pre-cooling, stretching, massage or vibration training as the priming strategies, or if interventions were performed at altitude or in hypoxic environments. Studies were assessed for methodological quality at the study level using the Physiotherapy Evidence Database (PEDro) scale. Results: Twenty-nine studies satisfied the eligibility criteria and were included in this review. Studies were categorised as resistance training; cycling; running; and other strategies. Resistance training using heavy loads at low volumes increased strength and power measures following a 4-6 h recovery, with limited improvements observed following shorter (1-3 h) and longer (6-12 h) recovery periods. Running-based sprint priming led to improvements in subsequent sprint and repeat sprint performance following a 5-6 h recovery, whereas cycling improved counter-movement jump height in a single study only. No significant differences were reported in any performance measures following endurance-based running or cycling strategies. Physiological markers, such a hormone and blood lactate responses, showed mixed results between studies. Conclusions: High-intensity low-volume resistance training leads to a greater physiological and performance response than high-volume resistance training. Maximal running sprints may be more effective than maximal cycling sprints due to an increased physiological demand; however, loading protocols must also be considered in conjunction with exercise volume and movement specificity to achieve a beneficial response for subsequent performance. There is limited evidence to suggest endurance cycling or running exercise is beneficial as a priming strategy.